Filaments and ionized gas in the vicinity of 3C 244.1 - Feinstein Baigorri, Carlos (2002)
We present results of Hubble Space Telescope observations of the radio galaxy 3C 244.1. The broad-band F702W (R) and F555W (V) images (WFPC2/PC) show an elliptical galaxy, and gaseous filaments and blobs surrounding it. In the narrowband ramp filter, dominated by [O III] λ5007, these filaments are bright and have the same morphology as the broadband images. To the south, the filaments have a cone-shaped structure, and the radio jet is located at the center of this cone. To the north of the galaxy, the structure is found near the nucleus of the galaxy within its elliptical profile. From the photometry, the two brighter structures seem to be extended narrow-line emission regions. A comparison with diagnostic line ratios shows that the observed emission is consistent with interactions between the expanding radio jet and the local denser medium.